3D-printed hyaluronic acid hydrogel scaffolds impregnated with neurotrophic factors (BDNF, GDNF) for post-traumatic brain tissue reconstruction - Mishchenko, Tatiana A.; Klimenko, Maria O.; Kuznetsova, Alisa I.; Yarkov, Roman S.; Savelyev, Alexander G.; Sochilina, Anastasia V.; Mariyanats, Alexandra O.; Popov, Vladimir K.; Khaydukov, Evgeny V.; Zvyagin, Andrei V.; Vedunova, Maria V. (Frontiers in Bioengineering and Biotechnology, 2022)
Brain tissue reconstruction posttraumatic injury remains a long-standing challenge in neurotransplantology, where a tissue-engineering construct (scaffold, SC) with specific biochemical properties is deemed the most essential building block. Such three-dimensional (3D) hydrogel scaffolds can be formed using brain-abundant endogenous hyaluronic acid modified with glycidyl methacrylate by employing our proprietary photopolymerisation technique. Herein, we produced 3D hyaluronic scaffolds impregnated with neurotrophic factors (BDNF, GDNF) possessing 600 kPa Young's moduli and 336% swelling ratios. Stringent in vitro testing of fabricated scaffolds using primary hippocampal cultures revealed lack of significant cytotoxicity: the number of viable cells in the SC+BDNF (91.67±1.08%) and SC+GDNF (88.69±1.2%) groups was comparable to the sham values (р>0.05). Interestingly, BDNF-loaded scaffolds promoted the stimulation of neuronal process outgrowth during the first 3 days of cultures development (day 1: 23.34±1.46 µm; day 3: 37.26±1.98 µm, p<0.05, vs sham), whereas GDNF-loaded scaffolds increased the functional activity of neuron-glial networks of cultures at later stages of cultivation (day 14) manifested in a 1.3-fold decrease in the duration coupled with a 2.4-fold increase in the frequency of Ca2+ oscillations (p<0.05, vs sham). In vivo studies were carried out using С57BL/6 mice with induced traumatic brain injury, followed by surgery augmented with scaffold implantation. We found positive dynamics of the morphological changes in the treated nerve tissue in the post-traumatic period, where the GDNF-loaded scaffolds indicated more favorable regenerative potential. In comparison with controls, the physiological state of the treated mice was improved manifested by the absence of severe neurological deficit, significant changes in motor and orienting-exploratory activity, and preservation of the ability to learn and retain long-term memory. Our results suggest in favor of biocompatibility of GDNF-loaded scaffolds, which provide a platform for personalized brain implants stimulating effective morphological and functional recovery of nerve tissue after traumatic brain injury.